Peran Kebijakan Publik Dalam Tata Kelola Pemerintahan Yang Baik Di Distrik Mamberamo Tengah Kabupaten Mamberamo Raya - Isak Bonai; Rossy Lambelanova (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
In essence, public policies in a good governance system are actions or steps taken by the government to ensure openness, accountability and public participation in the decision-making process. That public policy in a good governance government system has several meanings, including: Public policy is implemented openly and transparently to the public. Information related to policies, decision-making processes and policy implementation must be easily accessible to the public. The government is responsible for the policies produced and implementing these policies appropriately. The government also ensures accountability to the community in the use of public resources. Public policy must be responsive to the needs and aspirations of society. The government must be able to respond to community problems or complaints with appropriate solutions and policies. The community is given the opportunity to participate in the decision-making process. The government must involve them actively in planning, designing and implementing public policy. Public policies must be fair and side with all groups of society without discrimination. The main goal is to improve the welfare of all people by reducing social and economic disparities. Thus, public policy in a good governance government system aims to support the creation of good government, convince the public that government decisions are based on the public interest, and encourage active public participation in the decision-making process. The problem studied in this research is, how is the implementation of the principles of good governance in the Mamberamo Raya Regency Government with a study focus on three specific indicators, namely Transparency, Law Enforcement and Accountability. Initial. The main instrument determined in this research is through interviews with a number of informants who are considered to have capacity in the problems that are the focus of the study in this research. Data processing and analysis techniques are carried out in stages: data reduction, data display and data verification or drawing conclusions. The research results show that the three indicators are as follows: 1). In terms of transparency indicators, so far the achievements have been relatively good, because the government always strives to provide the necessary information and data to the public or people who need it; 2) in terms of law enforcement indicators as a reflection of good governance, so far the achievements have been relatively good, although not yet optimal, especially in terms of increasing employee discipline, which has not yet experienced maximum improvement, specifically in terms of activity in the office; 3) The accountability indicator has so far gone quite well. What is of particular concern for this indicator is the timeliness in compiling and submitting accountability reports from employees to management, which sometimes still experiences delays.